Evaluation of Physiological Parameters and Antimicrobial Properties of Pleurotus eous - Negi, Vasundhra; Jarial, R. S.; Jarial, Kumud (International Journal of Bio-resource and Stress Management, 2025)
The present investigation was carried out during September, 2021–March, 2022 at the laboratory of Department of Plant Pathology, College of Horticulture and Forestry, Neri, Hamirpur, Himachal Pradesh, India to study physiological parameters and antimicrobial properties of Pleurotus eous. Out of seven different solid and liquid media under study, malt extract medium was found to be the best with maximum diametric growth (83.25 mm), growth rate (13.04 mm day-1) and biomass (1591.47 mg) however, minimum diametric growth (49.57 mm), growth rate (7.43 mm day-1) and biomass (89.83 mg) was recorded in yeast malt media. Among nine different pH levels under study, the maximum diametric growth (83.25 mm) and growth rate (13.04 mm day-1) was recorded at 7.5 pH level while, minimum diametric growth (60.92 mm) and growth rate (9.32 mm day-1) was recorded at pH level 9.0. Further, 25°C was found to be the best for the maximum diametric growth (82.25 mm) and growth rate (12.88 mm day-1) of P.eous and minimum diametric growth (14.77 mm) and growth rate (1.55 mm day-1) was recorded at 35°C among different temperature regimes under study. Among different nitrogen, carbon sources and trace elements under study, sodium nitrate (114.04 mg), starch (171.82 mg) and ferrous sulphate (115.60 mg) respectively, were found to be the best with highest biomass while minimum biomass among different nitrogen, carbon sources and trace elements was recorded in glycine (36.13 mg), maltose (82.67 mg) and ammonium molybdate (23.77 mg), respectively.